THE RELATIONSHIP OF THE SCR WITH PARAMETERS OF RADIO BURSTS AND CME - Isaeva, E. A. (Одеські астрономічні публікації, 2018)
The relationship the intensity of the proton flux Ip of solar cosmic rays (SCR) with the parameters of continual radio bursts of the IV type, with the speed of coronal mass ejections (CME) of VCME, as well as with the parameters of slowly drifting radio bursts of type II is investigated. Comparative analysis showed that for the vast majority of proton events a strong correlation of the intensity of the proton flux Ip with the integral flux ∫Fμdt of microwave bursts and the CME velocity VCME is observed, where the correlation coefficient r between the investigated parameters is 0.80 and 0.72, respectively. Earlier, the author reported on a strong connection between the integral flux ∫Fμdt of the microwave bursts and the CME velocity VCME, where the correlation coefficient r between the investigated quantities is about 0.80. The strong connection between the intensity of the proton flux Ip and the integral flux ∫Fμdt of microwave bursts and the speed of the CME, as well as the strong connection between the integral flux ∫Fμdt of the microwave bursts and the CME velocity VCME, attests about the common origin of SCRs and CMEs during proton flares. In this paper it is also shown that there is a strong relationship between the intensity of the proton flux Ip and the parameter of type II burst VII, which characterizes the shock front displacement velocity. Moreover, the relationship between the intensity of the proton flux Ip and the parameter VII depends to a large extent on the frequency f2 of the maximum of the type II radio burst on the second harmonic at a given time t and on the energy of the protons Ep. The maximum correlation between the proton flux Ip and parameter VII is observed for protons with an energy Ep>30 MeV and for the upper frequency f2 in the range 25-60 MHz.